INTEGRATING GENRE-BASED AND PROCESS WRITING (A Reflection of Contextual Teaching and Learning) - Monalisa, Monalisa (Reflective, 2012)
The progress of approaches in language instruction is line with general development of educational theory and practice that take learners as the main concern. Then the selection of content and learning experience is corresponded to the learnersâ need, want, and lack since language instruction will be significant as learners are actively engaged in. Meaning is constructed by learners when their learning experiences link to the real world. Such meaningful learning is the philosophy of Contextual Teaching and Learning (CTL). In the teaching of writing, the integrated genre and process writing may reflect this contextual learning. The cyclical process of producing a text from modeling the target genre, narrowing a topic, generating ideas, outlining, drafting, peer editing, to producing final draft may reflect the principles and components of CTL: constructivism, questioning, inquiry, learning community, modeling, authentic assessment, and reflection.